Beginning Perl programming : from novice to professional - Rothwell, William (Apress, 2019)
This is a book for those of us who believed that we didn't need to learn Perl, and now we know it is more ubiquitous than ever. You'll see that Perl has evolved into a multipurpose, multiplatform language present absolutely everywhere: heavy-duty web applications, the cloud, systems administration, natural language processing, and financial engineering. This book provides valuable insight into Perl's role regarding all of these tasks and more giving you a great start in your Perl programming adventure.